Pengembangan Budaya Organisasi Sekolah Swasta Unggul - Putri Wulandari; Piter Joko Nugroho (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2020)
Abstract: This study aims to describe the development of excellent private middle school (SMPS) organizational culture in Palangkaraya City, viewed from aspects: (1) positive values that underlie the development of school organizational culture, (2) the strategy of internalizing positive values in the development of school organizational culture, ( 3) supporting and obstacles factors in the development of school organizational culture, and (4) the role of stakeholders in supporting the development of school organizational culture. This study used qualitative approach with case study design. The subjects of this study were the founder of the Golden Christian School (GCS) SMPS, the school principal, teachers, and school stakeholders. Data collected through observation, in-depth interviews and documentation studies. Data analysis techniques using interactive model is through data reduction, data presentation, conclusions drawing, and data verification. Validation of data in this study uses credibility, transferability, dependability and confirmability. The results of this study showed that the school organizational culture in SMSPS GCS was developed by basing on the values of Christianity as the main foundation in shaping the character and culture of school organizations. Through internalization strategies that are realized in various school policies and programs, positive values that are believed by schools to be embedded within students which ultimately shape school organizational culture and are able to make SMPS GCS as the excellent private school in Palangka Raya City.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan pengembangan budaya organisasi Sekolah Menengah Pertama Swasta (SMPS) unggul di Kota Palangka Raya, dilihat dari aspek: (1) nilai-nilai positif yang mendasari pengembangan budaya organisasi sekolah, (2) strategi internalisasi nilai-nilai positif dalam pengembangan budaya organisasi sekolah, (3) faktor pendukung dan kendala dalam pengembangan budaya organisasi sekolah, dan (4) peran stakeholder dalam mendukung pengembangan budaya organisasi sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi kasus. Subjek penelitian ini adalah Pendiri yayasan SMPS Golden Christian School (GCS), Kepala sekolah, Guru, dan Stakeholder sekolah. Data penelitian dikumpulkan melalui observasi, wawancara mendalam dan studi dokumentasi. Teknik analisis data menggunakan interactive model reduksi data, penyajian data, penarikan kesimpulan, dan verifikasi data. Pengabsahan data dalam penelitian ini menggunakan credibility, transferability, dependability dan confirmability. Hasil penelitian menunjukan bahwa budaya organisasi sekolah di SMPS GCS dikembangkan dengan mendasarkan pada nilai-nilai ajaran agama Kristen sebagai landasan utama dalam pembentukan karakter dan budaya organisasi sekolah. Melalui strategi-strategi internalisasi yang direalisasikan dalam berbagai kebijakan dan program sekolah, nilai-nilai positif yang diyakini sekolah tertanam dan melekat dalam diri peserta didik yang pada akhirnya membentuk budaya organisasi sekolah serta mampu menjadikan SMPS GCS sebagai sekolah swasta unggul di Kota Palangka Raya.